PEMBAGIAN KERJA SECARA GENDER DALAM PEMBERDAYAAN PANGAN LOKAL (STUDI KASUS DI DESA MOROREJO KECAMATAN TEMPEL KABUPATEN SLEMAN) - Mesalia Kriska (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2016)
ABSTRACTThis research aims to know about gender division of household labor in the empowerment of local food in Tempel Sub-District, Sleman Regency. Research method that is used was qualitative methods with case study approach. This research held in Mororejo Village, Tempel Sub-District. This location selected purposively because that village is the only one village which has the group of local food empowerment. Data gathered by participatory observation, interview, and documentation. The results showed that women dominated in every empower activity, that is training of local food processing, arisan, local food contests, and making the product at home. Man in household only involved in a hard work that need more power, like harvesting the cassava as a main ingredient and support activity for his wife, that is accompany his wife to go shopping at traditional market. In this case, there was gender relations in the empowerment activity of local food.